2022
DOI: 10.1186/s13071-022-05467-5
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of primary, secondary and suspected vectors to Plasmodium vivax and Plasmodium falciparum infection in Ethiopia

Abstract: Background Insecticide-based vector control interventions in combination with case management with artemisinin-based combination therapy has reduced malaria incidence and prevalence worldwide. Current control methods focus on the primary malaria vectors, Anopheles gambiae sensu lato (s.l.) and the An. funestus group; however, the impact of secondary and suspected vectors has been either sidelined or received limited attention. Defining the susceptibility of secondary, suspected vector species t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…pharoensis and An. funestus have been reported to be secondary or suspected malaria vectors in Ethiopia [ 66 ]. We detected An.…”
Section: Discussionmentioning
confidence: 99%
“…pharoensis and An. funestus have been reported to be secondary or suspected malaria vectors in Ethiopia [ 66 ]. We detected An.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recent unpublished data from circumsporozoite enzyme-linked immunosorbent assay (CSP-ELISA) and an artificial infection experiment using a membrane feeding assay showed that Ethiopian populations of An. coustani is susceptible to both Plasmodium falciparum and P. vivax [28]. Molecular species identification was conducted only for pyrethroid resistant samples…”
Section: Strength and Limitation Of The Studymentioning
confidence: 99%
“…For instance, recent unpublished data from circumsporozoite enzyme-linked immunosorbent assay (CSP-ELISA) and an artificial infection experiment using a membrane feeding assay showed that Ethiopian populations of An. coustani is susceptible to both Plasmodium falciparum and P. vivax [28]. However, there is a paucity of information on the bionomics, seasonal abundance, insecticide susceptibility status and vectorial capacity of secondary and suspected vectors in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Though secondary malaria vectors are considered to play minor roles in malaria transmission [3], their potential vectorial capacity and competence vary according to locality and season [4]. However, studies on the role of secondary and suspected vectors are limited or entirely missing in Ethiopia, possibly due to the extremely low infection rate (IR) or because no infections were reported [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Arti cial infection experiment using membrane feeding assay showed the Ethiopian populations of An. coustani is susceptible to both Plasmodium falciparum and P. vivax [7].…”
Section: Introductionmentioning
confidence: 99%